The auditing game: the dark side of the private provision of a public good - Thomas Ehrmann; Aloys Prinz (European Journal of Law and Economics, 2023)
The aim of auditing is to protect active and potential investors from accounting fraud. Nevertheless, as many auditing scandals have demonstrated, auditing has a dark side. Correct auditing is a public good provided by private auditing firms, but these firms are paid by the enterprise being audited. Therefore, audit firms may be dubbed as agents of two principals, the audited firm and the public. Reputation theory conjectures that auditors are disincentivized from performing shallow and fraudulent auditing because of reputational concerns and associated reputational costs. However, empirical evidence does not support this claim. While it may be irrational for a large audit firm (such as Arthur Andersen LLP) to sacrifice its reputational capital for a single client by doing superficial audits (such as WorldCom), it may be quite rational for the auditing firm's engagement partners to do so. The result might be a conspiracy against the public and investors. Because of an inelastic supply of experienced auditors and a highly concentrated market of big auditing firms, reputational losses due to auditing scandals for the audit firms' local partners and staff seem to be rather small. With a game theoretic model, we argue here that neither higher transparency nor higher fines for auditing failures may prevent such conspiracies. Therefore, legal regulations and court rulings can only change the expected fines for audit fraud, but they cannot solve the general problems arising from the symbiotic relationship between auditors and their client firms. As auditing firms may use the so-called expectation gap to protect themselves against legal claims of wrongdoing, avenues more suitable to deterring conspiracies by auditors and their client firms might include whistleblowing, short-selling investors and investigative journalism.
Keywords: D82; G18; K13; M41; M42; M48; 340; Auditing scandals; Auditing game; Cooperative behavior; Fraud; Reputation